PENERAPAN METODE TSTS (TWO STAY TWO STRAY) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MELAKUKAN PERBAIKAN ENGINE BERIKUT KOMPONEN-KOMPONENNYA SISWA KELAS X JURUSAN TEKNIK SEPEDA MOTOR SMK TAMANSISWA NAGGULAN 2015/2016 - Patrisius Meon Herin; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2017)
Patrisius Meon Herin, NIM. 2012006080. Implementation Method TSTS (two stay two stray) To Increase Motivation and Learning Outcomes Repairs Engine Following The Components Class X Engineering Motorcycles SMK Tamansiswa Nanggulan in academic year 2015/2016. Essay. Study Program of Mechanical Engineering, the Faculty of Education, University Sarjanawiyata Tamansiswa, Yogyakarta, 2016.The purpose of this research is knowing the process of implementing the method TSTS (two stay two stray) in an effort to enhance the liveliness and results of learning and determine whether the implementation of the method TSTS (two stay two stray) can enhance the liveliness and results of learning especially on learning improvement of engine and its components. This research is Classroom Action Research. Subject in this research were students of class X Motorcycle Engineering SMK Tamansiswa Nanggulan Kulon Progo, which has 21 students. The object of this research is the implementation process of the liveliness and the results obtained from the method TSTS on lesson improvement of engine and its components. Data collection techniques in this research conducted by observation and testing techniques. Data analysis technique implementation is done by qualitative descriptive . The results showed that after the applied method TSTS, liveliness and results of learning in lesson improvements engine and its components are increased so that the results of learning of students also increased. Results liveliness pre-test is 42% and after the action the cycle I 47%, the cycle II 65%, and the cycle III 76%. The percentage of whose value increases the cycle I 71%, the cycle II 75%, and the cycle III 85%. The response of students to the method TSTS (two stay two stray) was excellent. Looks percentage of every aspect with very high qualifications